2014
DOI: 10.1007/s13197-014-1269-y
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the shelf-life enhancement of potato stuffed parotha using thermal processing

Abstract: Convenient, ready-to consume thermally processed potato stuffed parothas retaining their natural sensory attributes have been developed. Response Surface Methodology was used to optimize the Stuffing: dough ratio along with other ingredients. Optimized Stuffed parothas were packed in indigenously developed retortable pouches and processed in a steam-air retort. The time-temperature history was recorded during heat processing using an Ellab data cum Fo recorder. The total processing time was 25 min with a Fo va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 9 publications
(5 reference statements)
2
9
0
Order By: Relevance
“…Browning intensity (OD) in choco quinoa nutri bar was carried out as per the method of Khan et al [15] by shaking 5 g of powdered bar sample with 70:30 ethanol/water for 2 h and measuring optical density at 420 nm.…”
Section: Measurement Of Browning Indexmentioning
confidence: 99%
“…Browning intensity (OD) in choco quinoa nutri bar was carried out as per the method of Khan et al [15] by shaking 5 g of powdered bar sample with 70:30 ethanol/water for 2 h and measuring optical density at 420 nm.…”
Section: Measurement Of Browning Indexmentioning
confidence: 99%
“…Aluminium laminates showed a greater decrease in moisture content than vacuum packaging, which could be attributed to the permeability properties of the aluminium laminates. Yadav et al (2009) and Khan et al (2014) observed a similar decreasing trend in frozen chapatti and potato-stuffed parothas. Wrapping food in impervious film reduces moisture loss; however, when food is wrapped loosely, moisture is deposited inside the packaging material as ice crystals.…”
Section: Physico-chemical Characterisation Of Potato Parantha During ...mentioning
confidence: 56%
“…After 9 months of storage, PV, FFA and TBA were found to be increased significantly from 5.12 to 19.24 meqO 2 Kg -1 fat; 0.75 to 1.69 % Oleic acid and 0.087 to 0.142 mg MA Kg -1 sample respectively. Khan et al (2014) reported an increase in PV, FFA and TBA contents in potato and paneer stuffed parothas during storage and attributed the increase due to the breakage of long fatty acid chain into individual fatty acid moieties and also increased lipid hydrolysis at elevated temperature. Although, during storage, there was a hydrolysis of lipids by the naturally occurring lipases, but during baking lipase activity was destroyed and therefore formation of free fatty acids in stored parothas must have resulted from the decomposition of hydroperoxide (Khan et al, 2014).…”
Section: Results and Discussion:-mentioning
confidence: 99%
“…Khan et al (2014) reported an increase in PV, FFA and TBA contents in potato and paneer stuffed parothas during storage and attributed the increase due to the breakage of long fatty acid chain into individual fatty acid moieties and also increased lipid hydrolysis at elevated temperature. Although, during storage, there was a hydrolysis of lipids by the naturally occurring lipases, but during baking lipase activity was destroyed and therefore formation of free fatty acids in stored parothas must have resulted from the decomposition of hydroperoxide (Khan et al, 2014). Processed stuffed parothas contained only solid, hence there had been no dilution of TBA reacting substances resulting in the increase in TBA values during storage.…”
Section: Results and Discussion:-mentioning
confidence: 99%
See 1 more Smart Citation